2003
DOI: 10.1055/s-2003-40447
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Bilobalide, a Component of Ginkgo biloba Extract (EGb 761®) in Global Brain Ischemia and in Excitotoxicity-induced Neuronal Death

Abstract: In this study, we compared the protective effect of bilobalide, a purified terpene lactone component of ginkgo biloba extract EGb 761, (definition see editorial) and EGb 761 against ischemic injury and against glutamate-induced excitotoxic neuronal death. In ischemic injury, we measured neuronal loss and the levels of mitochondrial DNA (mtDNA)-encoded cytochrome oxidase (COX) subunit III mRNA in vulnerable hippocampal regions of gerbils. At 7 days of reperfusion after 5 min of transient global ischemia, a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The goal of neuroprotection is to limit neuronal dysfunction or death after CNS injury, in an attempt to maintain the highest possible integrity of cellular interactions in the brain, thus minimizing the disturbance to the neural function [41]. According to the mechanisms of neuroprotection, the neuronal disorders can be treated by using different neuroprotection agents [42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57], such as antioxidants [42,43] and anti-inflammatory factors [44,45]. …”
Section: Update On Pathogenesis and Therapy For Neuronal Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of neuroprotection is to limit neuronal dysfunction or death after CNS injury, in an attempt to maintain the highest possible integrity of cellular interactions in the brain, thus minimizing the disturbance to the neural function [41]. According to the mechanisms of neuroprotection, the neuronal disorders can be treated by using different neuroprotection agents [42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57], such as antioxidants [42,43] and anti-inflammatory factors [44,45]. …”
Section: Update On Pathogenesis and Therapy For Neuronal Disordersmentioning
confidence: 99%
“…According to its mechanism, neuroprotection can be categorized into several mechanisms, such as: antioxidant (free radical trapper/scavenger) [42,43]; anti-inflammatory [44,45]; anti-excitotoxic [46]; apoptosis inhibitor [47]; gene expression modulator [48]; ion channel modulator [49,50]; metal ion chelator [51,52]; neurotrophic factor [53,54,55]; matrix metalloprotease inhibitor [56]; and combined mechanism (combining two mechanisms or more) [57]. …”
Section: The Mechanisms Of Neuroprotective Effects Of Chitosan Andmentioning
confidence: 99%
“…A standardized extract of Ginkgo biloba (EGb 761) has been shown to exhibit potent antioxidative and antiplatelet effects and could effectively reduce damage from cerebral ischemia [7681]. Besides, EGb 761 extract protected hippocampal neuronal and neuroglia cells against damage and enhanced the recovery of learning/memory impairments from cerebral ischemia/reperfusion in mice and rats [7983]. Furthermore, the Ginkgo extract has been reported to improve memory deficits and cognitive dysfunctions in various experimental models of memory disorders such as chronic stress, aging, and Parkinson's disease (PD) [8486].…”
Section: Therapeutic Implications For Vci With Traditional Chinesementioning
confidence: 99%
“…EGb 761 treatment attenuated cognitive impairments and prevented CA3 hippocampal neuronal loss in OVX/stress subjected female rats, as was observed with estrogen replacement [29, 30]. EGb 761 is an effective antioxidant that has been shown to provide protection against cardiovascular and neurological disorders [31, 32]. Many groups, including ours, have previously shown that EGb 761 attenuates brain damage in male rodents after permanent, transient and global models of ischemia [15, 16, 33].…”
Section: Discussionmentioning
confidence: 98%